An improvement within XFEM of the bonding between the enrichment area and the classical finite elements - Chahine, Elie; Laborde, Patrick; Renard, Yves (European Journal of Computational Mechanics, 2010)
We are interested in XFEM strain calculations of a cracked elastic body. It is already known that with XFEM, the approximation quality is distorted by the layer of elements lying between the singular enrichment area and the rest of the mesh. In the following work, we replace this transition layer by a "mortar" type integral bonding condition at the interface between the two areas. We prove how the proposed approach enhance significantly the approximation.